Structural change efforts of NATO and Turkey's role within the framework of the new institutional theory - Turkozu, Faruk; Akyurek, Server Sevil (Technium Social Sciences Journal, 2021)
In this article, NATO's historical and current change has been analyzed from the perspective of the new institutional theory. Turkey's position and role in the processes of the worldwide uncertainty and chaotic environment have been discussed in the same theoretical perspective. In addition, considering the situation of the EU and the USA especially during the pandemic process, NATO's approach towards China was evaluated. A secondary data technique was used in this qualitative study. According to the results of the research, it has been seen that the EU and the USA are losing their strategically targeted potential. In the chaotic period of the Covid-19 pandemic, it was determined that the EU countries and the USA avoided supporting each other, instead some eastern bloc countries lent a helping hand to European countries. With the perspective of increasing resilience by becoming non-polar, as the polar world is dragged into an environment full of increasing uncertainty and threats, it is predicted that it should be made possible globally to act based on cooperation rather than competition. In terms of Turkey's development as a global and local resistance, it would be helpful to develop an attitude compatible with the new paradigm is envisaged.